Effect of Deep Dormancy Temperature Cultivation on Meat Quality of Crucian Carp (Carassius auratus) - Yin Zhang; Linguo Wang; Yunlong Mu; Qing Zeng; Jianlin Jia; Pengcheng Zhang; Zhongli Pan (Foods, 2023)
To extend the survival of crucian carp (Carassius auratus) during transportation, the effect of deep dormancy temperature (DDT) cultivation on the crucian carp was investigated by measuring the respiratory rate, survival time, and effect of cooling speed on the meat quality. The results of the respiratory rate and survival time indicated that the DDT of the crucian carp was 1.6 °C. The cooling speed had a significant (p < 0.05) influence on the quality of the crucian carp meat, with a faster cooling speed resulting in a lower pH, L* value, a* value, gumminess, springiness, cohesiveness, stickiness, chewiness, CMP, and UMP content for the crucian carp meat, thus resulting in a lower sensory score for the crucian carp meat. A possible reason for the decrease in the quality of the crucian carp meat is that the faster cooling speed led to a strong stress response and higher anaerobic metabolism in the crucian carp. This can be supported by the contents of the blood glucose and lactic acid in the crucian carp treated with higher cooling speed being significantly (p < 0.05) higher than that of the control. Combining all the results of the cooling speed on the eating quality of the crucian carp meat, a cooling speed of 2 °C/h followed by 1 °C/h was suggested for the survival of crucian carp in transit.